Strike! - :::Creator::::::::::::; :::Contributor::::::::::::; :::Editor::::::::::::; University of California, Berkeley:::University place::::::::::::
Black silk screen print of a clenched fist, a symbol of militant resistance during the Civil Rights Movement. The clenched fist was used by students as a symbol of fighting back. The word "STRIKE!" appears at the bottom of the fist in bold black letters.